2010
DOI: 10.1007/s10522-010-9279-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging and exercise affect the level of protein acetylation and SIRT1 activity in cerebellum of male rats

Abstract: Aging is associated with a gradual decline in cognitive and motor functions, the result of complex biochemical processes including pre- and posttranslational modifications of proteins. Sirtuins are NAD(+) dependent protein deacetylases. These enzymes modulate the aging process by lysine deacetylation, which alters the activity and stability of proteins. Exercise can increase mean life-span and improve quality of life. Data from our laboratories revealed that 4 weeks of treadmill running improves performance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 42 publications
1
38
2
3
Order By: Relevance
“…The significant decrease of SIRT1 content was associated with a large change in lysine acetylation in the hippocampus, which could affect protein stability. 89 Acetylation of lysine residues could prevent the ubiquitination of the same residue, which would be important for the substrate recognition of proteasome-to-protein degradation. Therefore, overacetylation could impact protein stability and the half-life of proteins.…”
Section: Figmentioning
confidence: 99%
“…The significant decrease of SIRT1 content was associated with a large change in lysine acetylation in the hippocampus, which could affect protein stability. 89 Acetylation of lysine residues could prevent the ubiquitination of the same residue, which would be important for the substrate recognition of proteasome-to-protein degradation. Therefore, overacetylation could impact protein stability and the half-life of proteins.…”
Section: Figmentioning
confidence: 99%
“…Exercise appears to increase SIRT1 levels in the hippocampus [153], but not in the cerebellum [100]. However, data from other studies have shown that age-associated decreases in brain function can be alleviated by regular exercise [82,154].…”
Section: Regulation Of Sirtuins By Cr and Exercisementioning
confidence: 95%
“…The activation of SIRT1 resulted in enhanced degradation of FOXO3 by the proteasome system. Aging results in a loss of the activity of SIRT1, which is associated with increased levels of lysine acetylation in rat brain and skeletal muscle [42,82,100]. The level of acetylated lysine residues correlated well with that of carbonylation, which may mean that acetylated lysine could not have been ubiquitinated and degraded by proteasomes.…”
Section: Sirtuins In Protein Stability and Cellular Stress Responsementioning
confidence: 99%
“…In heart, age-related in SIRT1, decline is accompanied by a higher level of oxidative stress and the decrease in the expression of endogenous antioxidant enzymes and their regulators (Ferrara et al, 2008). In central nervous system, aging results in decreased activity of SIRT1 in cerebellum that leads to the increase in acetylation of protein residues specially affecting motor function (Marton et al, 2010). In cell culture models, cellular senescence induced by ionizing radiation is accompanied by the decrease in the levels of SIRT1 (Hong et al, 2010).…”
Section: Modulation Of Sirtuin Levelsmentioning
confidence: 99%